DRUG ENHANCEMENT, SYNERGISM AND ANTIFUNGAL ACTIVITY OF MICONAZOLE ASSOCIATED POLYGODIAL AGAINST CANDIDA ALBICANS - Santos, Vagner Rodrigues; de Souza Pinto, Livia SâmaraFranciele; de Borges, Bruno César; Kubo, Isao (International Journal of Research -GRANTHAALAYAH, 2017)
Miconazole has low toxicity, however, there is a high incidence resistance of Candida sp. In the search for new drugs or improve existing ones, the originating products of medicinal plants has been the target of constant studies. The aim of this work was to verifyinvitrosynergismand antifungal activity of miconazole associated with poligodial. Miconazole (MCZ) and Poligodial (P) were dissolved in dimethylsulfoxide (DMSO) 1% done successive dilutions of each product ranging from 25mg to 0,19mg/mL (Polygodial)(10-1 to 10-9mg / ml); 14mg to 0,10mg/mL (miconazole). Antifungal test were based by CLSI diffusion agar against C. albicans (ATCC 18804), C. albicans (LMB01) and C. albicans (LMB02), C. tropicalis (ATCC 18807),C. lusitaniae (ATCC 42720), C. krusei (ATCC 20405). The results had shown all compounds that were effective in inhibiting Candida species. However, the zones of inhibition in agar diffusion test were higher for Miconazole (16,83mm) and Polygodial (15,16mm) while the MIX showed lower inhibition zones (14,43mm) when compared with controls. MIX was more effective in MIC test, and lowest concentration were at 10-6 dilution (0,60mg / ml) compared to MCZ and P controls.